Self-Compassion Dan Stoikisme Sebagai Fondasi Regulasi Emosi Pasca Kegagalan Akademik: Kajian Filosofis Dalam Bimbingan Dan Konseling Siswa SMA - Pratama, Wiwid; Prasetya, Akhmad Fajar (Jurnal Ilmu Bimbingan dan Konseling, 2025)
Academic failure is a common experience among senior high school students and may lead to emotional distress when not accompanied by adaptive emotion regulation skills. This study aims to analyze the role of self-compassion and Stoic philosophy as foundations of emotion regulation among senior high school students following academic failure within the context of guidance and counseling. This research employed a Systematic Literature Review (SLR) of national and international scholarly articles published between 2019 and 2025 and selected based on their relevance to emotion regulation, academic failure, and adolescent development. The findings indicate that self-compassion helps students respond to failure more adaptively by reducing self-criticism and enhancing self-acceptance, thereby alleviating emotional distress. Meanwhile, Stoicism provides a cognitive–philosophical framework for emotion regulation through the principle of the dichotomy of control. The integration of self-compassion and Stoicism in guidance and counseling services, particularly through group counseling, has the potential to strengthen emotion regulation and promote the psychological well-being of senior high school students.